DIGITAL BRANDING STRATEGY FOR MSMEs TO INCREASE COMPETITIVENESS IN THE GLOBAL - Ashif Syaifullah (CURVE: Journal of Economic, Business and Accounting, 2026)
The era of globalization and the digital economy demands that Indonesian MSMEs adopt digital branding strategies to strengthen their competitiveness in the global market, where a strong online presence influences 70% of consumer purchasing decisions through platforms like Instagram and TikTok. Challenges such as low digital literacy, limited capital, and export regulations prevent only 15% of MSMEs from successfully penetrating the international market. This study aims to analyze effective digital branding strategies for MSMEs, encompassing brand identity, content, advertising, and global e-commerce, as well as the enabling and inhibiting factors for sustainable transformation. The study used a qualitative descriptive approach through semi-structured interviews with 10 MSMEs from the fashion, culinary, and craft sectors, supplemented by observations of social media, e-commerce, and secondary data from literature and government reports over three months. Thematic analysis identified strategic patterns, factors, and implications. The results show that integrated strategies such as unique USPs, multilingual SEO, UGC content, micro-influencers, and marketplaces like Etsy tripled revenue and expanded to 10 countries within 1-2 years, supported by access to technology and government training. Inhibiting factors include minimal digital literacy (60% of MSMEs) and export bureaucracy, with implications for increasing visibility by 70%, ROI by 40%, and achieving a target of 30 million digital MSMEs by 2029 through stakeholder synergy.